Tinjauan Literatur tentang Faktor Risiko, Pencegahan, dan Penanganan Palatoskizis (Celah Langit-Langit) - Firna, Bismi Rahma; Atifah, Yusni (TSAQOFAH, 2025)
Palatoschisis is a congenital craniofacial anomaly with significant clinical and social implications, particularly in developing countries where prevention and management efforts continue to face numerous challenges. This study aims to systematically review the scientific literature on risk factors, early detection methods, and management approaches for palatoschisis. A systematic literature review was conducted based on ten scholarly articles published in the past ten years, sourced from PubMed, ScienceDirect, and Google Scholar. Inclusion criteria consisted of articles in English or Indonesian that addressed the etiology, diagnosis, and treatment of palatoschisis. Thematic analysis was applied to categorize findings into key thematic areas. The review identified major risk factors including genetic mutations (e.g., IRF6 and MSX1), micronutrient deficiencies (folate and vitamin A), and exposure to teratogenic substances such as tobacco and pesticides. Early detection using 3D ultrasound was found to be effective for prenatal identification. Optimal management requires a multidisciplinary approach involving surgical intervention, speech therapy, and psychosocial support for both the child and their family. The study concludes by underscoring the importance of cross-sector collaboration in promoting comprehensive prevention and management strategies, as well as the need to ensure equitable access to healthcare services and public education to improve the quality of life for individuals affected by palatoschisis.